Evaluating Reproductive and Sexual Health Training for Red Cross Youth: The Kirkpatrick Model - Dewi Rahmadania; Elais Retnowati; Karta Sasmita; Hilma Fitriyani (Universitas Negeri Semarang, 2024)
In Indonesia, where cultural sensitivities and varying levels of awareness about sexual health exist, the need for tailored, culturally appropriate education is paramount. The Indonesian Red Cross (PMI) plays a pivotal role in community health initiatives, including sexual reproductive health education, by leveraging its wide network of volunteers. These volunteers are often on the frontline, engaging directly with the community, including adolescents, who are at a critical stage of developing attitudes and behaviors regarding their health. This study aims to evaluate the effectiveness of a sexual reproductive health training program for Indonesian Red Cross (PMI) volunteers in Langkat and Jombang districts, employing a mixed-methods approach based on the Kirkpatrick four-level evaluation model. The study utilizes an evaluative methodology with the Kirkpatrick model, involving data collection techniques through surveys, tests, interviews, and observations. It applies purposive sampling to 65 training participants, focusing on individuals who meet specific and relevant criteria. Data analysis is tailored to each level of Kirkpatrick's evaluation: Reaction, Learning, Behavior, and Results. Findings indicate a high level of participant satisfaction with the training material and its delivery, as well as an increase in knowledge and skills regarding adolescent sexual reproductive health. Despite significant improvements, the study identifies areas requiring enhancement. Evaluation success criteria were set using a Likert scale, allowing for objective and standardized measurement. The training program successfully enhanced the awareness and skills of PMI volunteers in addressing adolescent sexual reproductive health issues. This study provides essential insights for future improvements and development of training programs, emphasizing the importance of a comprehensive approach that involves technical, interpersonal, cultural aspects, and self-reflection in adolescent reproductive health education.